The Pioneering Inclusivity: A Narrative Study of the First Inclusive Raudatul Athfal in South Kalimantan - Pratiwi, Hardiyanti; Yarliani, Ikta; Haida, Rizki Noor (INKLUSI, 2024)
Inclusive education is indispensable for ensuring equitable educational opportunities and rights for children with special needs (CWSNs) to enhance their skills. However, maintaining inclusive schools encounters significant challenges, including limited resources and societal biases against CWSNs. This study centers on the establishment and operation of Ulumul Qur'an Al-Madani, the first inclusive Raudatul Athfal in South Kalimantan. Employing a qualitative narrative approach, data were gathered through in-depth interviews, document analysis, and participatory observation. The study highlights the crucial role of the school principal, bolstered by her family's property business and partnerships with therapists and experts in inclusive education, facilitated the school's transition to inclusivity. Despite encountering initial lack of support from the Ministry of Religion and the city government, the school achieved national acclaim for promoting inclusive education in South Kalimantan. This research underscores the principal's dedication and collaborative endeavors in promoting inclusive education and overcoming societal barriers for CWSNs. Pendidikan inklusif penting untuk memastikan kesempatan pendidikan yang adil dan hak-hak yang setara bagi anak-anak berkebutuhan khusus (ABK) untuk menstimulasi perkembangan mereka. Namun, menyelengggarakan sekolah inklusif menghadapi tantangan signifikan seperti sumber daya yang terbatas dan prasangka sosial terhadap ABK. Penelitian ini berfokus pada pendirian dan penyelenggaraan Ulumul Qur'an Al-Madani, Raudatul Athfal inklusif pertama di Kalimantan Selatan. Menggunakan pendekatan naratif kualitatif, data dikumpulkan melalui wawancara mendalam, analisis dokumen, dan observasi partisipatif. Penelitian ini menyoroti peran kunci kepala sekolah, yang didukung oleh bisnis properti keluarganya dan kolaborasi dengan terapis dan ahli pendidikan inklusif, yang mendukung transformasi inklusif sekolah tersebut. Meskipun awalnya tidak mendapat dukungan dari kementerian agama dan pemerintah kota, sekolah ini mendapatkan pengakuan nasional dalam memajukan pendidikan inklusif di Kalimantan Selatan. Penelitian ini menyoroti pentingnya dedikasi kepala sekolah dan upaya kolaboratif dalam mewujudkan pendidikan inklusif dan mengatasi hambatan sosial terhadap ABK.